Patient - and family- centered care practice among emergency nurses at Hue Central Hospital: A cross sectional mixed methods study - Thu, Mai Ba; Phuong, Nguyen Thi Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Patient -and family -centered care (PFCC) is widely encouraged but remains difficult to implement in emergency settings due to time pressure, severe and complex clinical conditions, and workforce overload, while evidence in Vietnam is still limited. This study aimed to examine the PFCC among emergency nurses at Hue Central Hospital and to explore barriers and challenges to its implementation. Methods: A cross sectional mixed methods study was conducted. Participants were nurses working in the Emergency Departments of Hue Central Hospital, with at least 6 months of employment and a valid practicing certificate; those who did not consent or were absent during the study period were excluded. The quantitative component assessed PFCC practice, while the qualitative component explored perceived barriers and challenges. Results: Among 121 nurses, 76% reported facilitating family participation, information provision, and collaboration in care; however, specialized support services were limited, including spiritual counseling (6.6%), psychological support (48.8%), funeral support (20.6%), and interpreter services (26.4%). PFCC practice did not differ by sex, professional qualification, years of experience, or job position (p>0.05) but differed across units (p=0.003). Key barriers related to overcrowding and limited facilities, family stress and financial constraints, and insufficient training and support services. Conclusions: PFCC has been implemented in the Emergency Departments of Hue Central Hospital but remains uneven across units and lacks important enabling supports. Strengthening training, optimizing staffing and task allocation, and expanding support services are needed to improve PFCC in emergency care.